Pengaruh Proses Rekrutmen Dan Seleksi Terhadap Kinerja Karyawan Departemen Meat Preparation Pada PT. Orsoindo Sejahtera - Mardianico Purna Ditya (JURNAL PUNDI, 2021)
Fast traslate Icon translate     Fast traslate Icon translate     Fast traslate Icon translate The purpose of this study is to determine the effect of the recruitment and selection process on employee performance, based on the results of tests that have been carried out it can be seen that the recruitment process has a t-value greater than the t-table value, this can mean that recruitment has a positive and significant effect on the performance of the meat preparation department employee at PT. OrsoindoSejahtera, as well as selection, selection has a t-value greater than the t-table value, this can be interpreted that the selection also has a positive and significant effect on the performance of the meat preparation department employees at PT. OrsoindoSejahtera